Production of Lipopeptide Biosurfactant by a Marine Nesterenkonia sp. and Its Application in Food Industry - Kiran, George S.; Priyadharsini, Sethu; Sajayan, Arya; Priyadharsini, Gopal B.; Poulose, Navya; Selvin, Joseph (Frontiers in Microbiology, 2017)
Biosurfactants are smart biomolecules which have wide spread application in medicines, processed foods, cosmetics as well as in bioremediation. In food industry, biosurfactants are used as emulsion stabilising agents, antiadhesives, and antimicrobial/antibiofilm agents. Nowadays biosurfactant demands in industries has increased tremendously and therefore new bacterial strains are being explored for large scale production of biosurfactants. In this study, an actinobacterial strain MSA31 was isolated from a marine sponge Fasciospongia cavernosa which showed high activity in biosurfactant screening assays such as drop collapsing, oil displacement, lipase and emulsification. Lipopeptide produced by MSA31 was found to be thermostable which was evident in differential scanning calorimetry analysis. The spectral data obtained in the Fourier transform infrared spectroscopy showed the presence of aliphatic groups combined with peptide moiety which is a characteristic feature of lipopeptides. The stability index of lipopeptide MSA31 revealed “halo-alkali and thermal tolerant biosurfactant” which can be used in the food industry. Microtiter plate assay showed 125µg/ml of lipopeptide was effective in reducing the biofilm formation activity of pathogenic multidrug resistant Staphylococcus aureus. The confocal laser scanning microscopic images provided further evidences that lipopeptide MSA31 was an effective antibiofilm agent. The antioxidant activity of lipopeptide MSA31 may be due to the presence of unsaturated fatty acid present in the molecule. The brine shrimp cytotoxicity assay showed lipopeptide MSA31 was non-toxic and can be used as food additives. Incorporation of lipopeptide MSA31 in muffin showed improved organoleptic qualities compared to positive and negative control. This study provides a valuable input for this lipopeptide to be used in food industry as an effective emulsifier, with good antioxidant activity and as a protective agent against S. aureus.